2020
DOI: 10.3390/molecules25194359
|View full text |Cite
|
Sign up to set email alerts
|

Pyrroloquinoline Quinone Inhibits Rotenone-Induced Microglia Inflammation by Enhancing Autophagy

Abstract: Neuroinflammation is a feature common to neurodegenerative diseases, such as Parkinson’s disease (PD), which might be responsive to therapeutic intervention. Rotenone has been widely used to establish PD models by inducing mitochondrial dysfunction and inflammation. Our previous studies have reported that pyrroloquinoline quinone (PQQ), a naturally occurring redox cofactor, could prevent mitochondrial dysfunction in rotenone induced PD models by regulating mitochondrial functions. In the present study, we aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 55 publications
4
15
0
Order By: Relevance
“…These results are in agreement with other work that evaluated the effect of CM from BV-2 cells on SH-SY5Y cells for other classes of protective compounds [ 43 , 44 ].…”
Section: Resultssupporting
confidence: 93%
“…These results are in agreement with other work that evaluated the effect of CM from BV-2 cells on SH-SY5Y cells for other classes of protective compounds [ 43 , 44 ].…”
Section: Resultssupporting
confidence: 93%
“…These results point toward a new role of PQQ in inducing mitophagy in MSCs, besides regulating mitochondrial biogenesis and mtROS, as shown by others ( 60, 72 ). Our findings here are consistent with a recent report showing that PQQ induces autophagy in human microglia by regulating LC3 maturation and Atg5 expression, independent of its effect on mitochondrial biogenesis ( 61 ). Further, in neuroblastoma cells and mice models, PQQ induces AMPK1 expression, which is a crucial regulator of autophagosome formation ( 62 ).…”
Section: Discussionsupporting
confidence: 94%
“…4A). Earlier studies have reported that PQQ attenuates mtROS and improves mitochondrial health, and increases autophagy (60)(61)(62), so based on these rational we choose PQQ in subsequent experiments to explore its role in alleviating mitochondrial health of MSC-Ob. Initially, we tested various time points of PQQ to find the optimal dose by looking at its effect in lowering the mtROS.…”
Section: Pqq Treatment Restores Impaired Mitophagy By Increasing Sequestration Of Damaged Mitochondria To Autophagosomesmentioning
confidence: 99%
“…The following effects of PQQ are the increase of gene expression of PGC1α and downstream targets such as TFAM [ 152 ]. In microglia, it was proved that PQQ neuroprotective properties have been reported by activation of PINK1/parkin-mediated mitophagy in rotenone-exposed cells [ 172 ]. In the case of melatonin, a neurohormone produced by the pineal gland, it has been observed that SIRT3 activity rises without increasing its expression in an atherosclerosis mouse model [ 134 ] or in cadmium-exposed HepG2 cells [ 153 ].…”
Section: Sirt Modulationmentioning
confidence: 99%